OUR AMERICA” AS AN EDUCATIONAL PLATFORM IN OUR CONTINENT (2013)
In January 1891 Jose Marti published the benchmark of his prose his essay “Our America”. The hypothesis stated in this paper identifies that work as a carrier of a great significance for education and culture in Latinoamerica. The purpose of our article is to show the direct link between the social and historical context was written and the thoroughness of Jose Marti´s discourse. The methodology used is based on the consulting, analyzing and interpreting available sources; in this case the Complete Works of Jose Marti, as published in 1963, on 28 volumes and the Critical Edition of Jose Marti´s work written by CintioVitier. It is concluded that the conception and writing of the essay “Nuestra America” (“Our America”) at the end of the eighth decade of the 19th century is an essential landmark for the study of the historic development of Latin-American education and culture. Our America calls for a common cause with the oppressed and it conceptualizes race mixture as the essence of our culture. It conceives education of America´s native man in concord with Nature, culture, history and aspirations for freedom as well as the development of our nations on the social basis upon which they were built up. It is an authentic and coherent discourse favoring the determination of a trunk of cultural referents necessary for the education of Latin-American man.